A parametric freckle model for faces - Schneider, Andreas; Egger, Bernhard; Vetter, Thomas (Proceedings - 13th IEEE International Conference on Automatic Face and Gesture Recognition, FG 2018, 2018)
We propose a novel stochastic generative parametric freckle model for the analysis and synthesis of human faces. Morphable Models are the state-of-the-art generative parametric face models. However, they are unable to synthesize freckles which are part of atural face variation. The deficiency lies in requiring point-to-point correspondence on the texture pixels. We propose to assume a correspondence between freckle density and not the freckles themselves. We propose a model that is stochastic, generative, and parametric and generates freckles with a point process according to a density and size distribution. The resulting model can synthesize photo-realistic freckles according to observations as well as add freckles to existing faces. We create more realistic faces than with Morphable Models alone and allow for detailed face pigment analysis.
CRIS-Team Scopus Importer:2021-09-15
Keywords: Face synthesis; Freckle synthesis; Morphable model